Державне регулювання розвитку приватної освіти на Катеринославщині у першій половині ХІХ ст. - Прокопенко, Леонід (My University, 2019)
У статті досліджено державне регулювання діяльності приватних закладів освіти та її вплив на розвиток приватної освіти на Катеринославщині в першій половині ХІХ ст. Особливу увагу приділено розгляду процесу формування внормативно-правова база приватної освіти. У ньому викладено основні положення «Статуту навчальних закладів, підлеглих університетам» від 5 листопада 1804 р., «Статуту про гімназії та училища повітів і волостей» від 8 грудня 1828 р., «Положення про приватні навчальні заклади» від 12 січня 1804 р. , 1835 р., «Положення про домашніх вихователів і вчителів» 1834 р., яке регулювало порядок відкриття приватних навчальних закладів, організацію в них навчального процесу, забезпечення домашнього виховання тощо.

The article examines the state regulation of the activity of private educational institutions and its influence on the development of private education in Katerynoslav region in the first half of the nineteenth century. Particular attention is paid to considering the process of formation of the normative and legal base of private education. It describes the main provisions of the «Statute of educational institutions, subordinated to universities» dated November 5, 1804, «Statute of gymnasiums and schools of counties and parishes» dated December 8, 1828, «Regulations on private educational institutions» dated January 12, 1835, «Regulations on home tutors and teachers « dated 1834, which regulated the procedure for the opening of private educational institutions, organization of educational process in them, providing home education, etc.
State regulation of the development of private education in Katerynoslav region in the first half of the ХІХth century
Keywords: державне регулювання; чоловічі і жіночі приватні пансіони; домашні наставники і вчителі; state regulation; women’s and men’s private boarding houses; home tutors and teachers